AVR-AgDb: A Plant-Based Antiviral Repository to Minimize the Detrimental Effects of Frequent Viral Outbreaks and the Next Pandemic - Tilak Chandra; Sudip Kumar Dutta; Bibek Saha; Sarika; UB Angadi; Anil Rai; Dinesh Kumar; Mir Asif Iquebal (Journal of the Indian Society of Agricultural Statistics, 2026)
There is an imperative need to investigate less toxic antiviral phytomolecules than nucleic acid analogs, enzyme inhibitors, or synthetic molecules as antiviral therapeutics. Agricultural crops and their secondary metabolites have been well known for their healing and immunity-boosting properties throughout the globe since human civilization. A recent global pandemic, COVID-19, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has become one of the most devastating challenges for humans, compounded by increasing diffusion due to migration, global travel, and urbanization. Even before this, about >650K annual deaths had been due to seasonal viral flu disease alone. Dramatic mutations in viruses and the time needed in vaccine development have made the world realize nutrition-immunity intervention as a pragmatic preventive approach for most human viral diseases. In the telecommunications era, an efficient, user-friendly database for searching antiviral plants and their constituents is a prerequisite. Such a database will also facilitate post-COVID economic resilience in the agricultural system. It may also accelerate the research and development of eco-friendly antiviral molecules from natural resources. It further provides classified antiviral molecules with their specific names and structure, their modes of action, and model organisms studied, along with respective literature references. This information can be accessed or retrieved plantwise, viral disease-wise and chemical compound class/sub-class-wise using a URL (https://avragdb.abrl.in/). It comprehensively comprehends about >350 molecules with antiviral properties from >500 plants of medicinal and agricultural importance. The database could be useful for phytotherapy research and spreading the accountability of plant-based antiviral formulations.